Fast TV-PRO-seq: Accelerated and Streamlined Protocol for Timing RNA Polymerase Pausing - Zhang, Jie; Liang, Zhixian; Sun, Mingxin; Hebenstreit, Daniel; Zhang, Shaohui (Bio-protocol, 2025)
Transcriptional pausing dynamically regulates spatiotemporal gene expression during cellular differentiation, development, and environmental adaptation. Precise measurement of pausing duration, a critical parameter in transcriptional control, has been challenging due to limitations in resolution and confounding factors. We introduce Fast TV-PRO-seq, an optimized protocol built on time-variant precision run-on sequencing (TV-PRO-seq), which enables genome-wide, single-base resolution mapping of RNA polymerase II pausing times. Unlike standard PRO-seq, Fast TV-PRO-seq employs sarkosyl-free biotin-NTP run-on with time gradients and integrates on-bead enzymatic reactions to streamline workflows. Key improvements include (1) reducing experimental time from 4 to 2 days, (2) reducing cell input requirements, and (3) improved process efficiency and simplified command-line operations through the use of bash scripts. Key features • Reduces experimental duration from 4 to 2 days via on-bead enzymatic reactions and streamlined workflows. • Enables single-nucleotide resolution pausing time mapping using time-variant biotin-NTP run-on with saturation kinetics. • Compatible with reduced cell input (10 -10 cells) and sarkosyl-free conditions for improved experimental feasibility. • Integrates bash scripts and simplified commands for enhanced reproducibility and reduced computational complexity.